Complex, high-risk thoracic surgery—does risk always outweigh the benefit or can we manage it safely? - Irons, Joanne Frances; Martinez, Guillermo (Video-Assisted Thoracic Surgery, 2017)
With the advances in diagnostic imaging and surgical techniques for lung diseases and cancers more patients are presenting for thoracic surgery. Often patients are old with multiple comorbidities, which predispose them to significant and life threatening complications. The decision to operate on these patients requires careful assessment and planning by the multidisciplinary thoracic team. In this review we aim to present the preoperative assessment and investigations, the current risk scoring systems in place and the optimisation of these patients in attempt to lower the risk and to allow informed decision making surrounding their appropriate treatment. We also discuss specific high-risk procedures and interventions which may be utilised in specialist centres to allow surgery to take place in unique situations and complex patients.